Faktor yang Memengaruhi Kualitas Audit di Indonesia (Tinjauan Literature Sistematis) - Ayem, Sri; Putri, Fuadhillah Kirana; Jannah, Siti Nur; Rewur, Gabriela Serafina (-, 2024)
There are still many cases related to audit quality involving the public accounting profession in various financial reporting scandals. In order to mitigate the risk of significant inaccuracies in a company's financial reports, it's essential to conduct a meticulous audit meeting high-quality standards. This scholarly investigation endeavors to discern the specific elements influencing the quality of audits conducted in Indonesia. Employing a Systematic Literature Review via Harzing's Publish or Perish 8 software on Google Scholar, this study relies on secondary data derived from 100 articles spanning the period from 2013 to 2023. The findings, illustrated through a Pie Chart, unveil a spectrum of 36 factors impacting the quality of audits. Notably, pivotal factors influencing audit quality include audit tenure, accounting for 14%, independence at 11%, and competence at 10%. Future research endeavors in the realm of auditing quality could delve into previously underexplored aspects like healthy lifestyle habits, emotional intelligence, altruistic behavior, litigation risk, and concentration within the audit market.